Implementation of Nature-Based Deep Learning to Develop Ecoliteracy Skills in Early Childhood - Wildan Alim Nurhidayah; Abda Billah Faza Muhammadkan Bastian (Journal of General Education and Humanities, 2026)
This study aims to implement and evaluate the Nature-Based Deep Learning model in developing ecoliteracy skills in early childhood. Using a qualitative descriptive approach and field research design, the study was conducted at BA Aisyiyah Kalilandak involving 18 children aged 5–6 years. Data collection techniques included observation, interviews, and documentation. The model was implemented through three sequential phases: authentic exploration, guided reflection, and conceptual application. The results showed significant improvements in children's cognitive abilities, including observation, classification, and understanding of ecological relationships, as well as the development of empathy, environmental responsibility, and pro-environmental behavior. The structured integration of direct experiences in nature with reflective processes proved effective in fostering deep ecological understanding and agency in children. Pedagogically, this study emphasizes the role of teachers as facilitators of reflection and the importance of a systematic, nature-based learning design to achieve meaningful and sustainable educational outcomes.